Perancangan Video Profile jurusan usaha layanan pariwisata di SMK Negeri 2 Batam - Sugianto Sugianto; Indasari Deu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
A majors school in Batam Named SMK Negeri 2 Batam which has a variety of learning majors for new students, this school was founded on June 1 2006 and is a school that provides various majors to hone students' talents, and has a Vision to become a Management and Tourism Business Training Education Center that has professional and noble graduates and is a reference for other agencies with international standards in 2020. The survey said that the problem is there is no media to promote school programs, especially in the field of tourism majors and make a video with the concept of a company profile which will be uploaded on the school's social media. The aim is to introduce the Batam 2 State Vocational School and the tourism department to the community. There are various stages that must be carried out, such as the pre-production stage, the production stage, and the post-production stage, shooting using iPhones and drones and using the Wondershare Filmora 2022 software. From the results of implementing videos that have been published on Youtube and other social media, it will help the school in improving the school's image to the surrounding community and promoting the background of the school.